P113 Sildenafil in the treatment of group 3 pulmonary hypertension. (12th November 2019) - Sathianandan, S; McCabe, C; Dimopoulos, K; Kempny, A; Harries, C; Wells, AU; Semple, T; Wort, SJ; Price, LC
Abstract : Introduction and objectives: Pulmonary hypertension (PH) in patients with chronic lung diseases (Group 3 PH) confers a worse prognosis. Treatment with pulmonary vasodilators, such as Sildenafil, remains controversial. Whilst some studies report a benefit, few select patients with severe PH (mean pulmonary artery pressure [mPAP] ≥35 mmHg) and there are concerns regarding inhibition of hypoxic pulmonary vasoconstriction and impaired gas exchange in this patient group. Our aim was to assess the short-term outcomes in patients with severe Group 3 PH treated with Sildenafil. Methods: A retrospective review of patients with group 3 PH treated with Sildenafil at a tertiary PH centre. Baseline and follow-up data were collected including haemodynamics from right heart catheterisation (RHC), echocardiography parameters, serum BNP levels, WHO functional class, 6-minute walk distances (6MWD) and EmPHasis-10 (E-10) scores. Sildenafil was initiated at 12.5–25mg TDS. Data are mean±SD or median (range). Results: 22 patients with group 3 PH were reviewed (mean age 65±11 years, 11 males). Underlying diagnoses included COPD (23%), CPFE (27%) and ILD (36%). Baseline lung function (% predicted) was FEV1 69.8±24.1%, FVC 80.8±28.2% and TLCO 22±5.5%. The mPAP pre-treatment was 46.1±10 mmHg and pulmonary vascular resistance (PVR) 12 (range 6–23) wood units. Median follow-up between initiation of Sildenafil and re-assessment was 4 (range 1–26) months. 8 patients had repeat RHCs. There were no statistically significant improvements in haemodynamics (mPAP, cardiac output or PVR), echo findings or BNP. An improvement in 6MWD was seen, from 235± 66m to 306±65m (p=0.023). 14 patients reported an improvement in symptoms, however the improvement in E-10 scores was minimal and not significant (-2 points, p=0.484) and there was no improvement in WHO functional class. 3 patients experienced adverse effects (deterioration of oxygenation and hypotension). Conclusions: Sildenafil appears to be well tolerated and safe in most patients with an improvement in 6MWD observed. Larger randomised controlled trials with longer follow-up are warranted to assess its use further and identify baseline characteristics of 'responders' versus 'non-responders'. We aim to identify 'responders' in our group and define a phenotype based on data collected above and CT imaging.